Stable Isotope Sequential Derivatization for Linkage-Specific Analysis of Sialylated N‑Glycan Isomers by MS - Peng, Ye; Wang, Limeng; Zhang, Ying; Bao, Huimin; Lu, Haojie (Analytical chemistry (Washington), 2019)
Sialylated N-glycans play pivotal role in several important biological and pathological processes. Their sialyl-linkage isomers, mostly α-2,3- and α-2,6-linked, act differently during the cellular events and several diseases. While mass spectrometry (MS) technology is a powerful tool in N-glycome analysis, it still suffers from an inability to distinguish linkage isomers of native N-glycans. Herein, we described a sequential selective derivatization method, by which α-2,6- and α-2,3-linked sialic acids are sequentially labeled with methylamide incorporated with a different stable isotope. Isobaric labeling avoids inducing bias in ionization efficiency and chromatographic behavior. In optimized reaction conditions, high derivatization selectivity (∼99%) was achieved for both α-2,3- and α-2,6-linked sialic acid. High accuracy of quantitation within a dynamic range of 2 orders of magnitude and high reproducibility (CV < 20%, n = 3) were demonstrated using standard glycans and multisialylated N-glycans. Finally, this method was applied in profiling the N-glycome of serum from CRC patients, where a level of six sialyl-linkage isomers were found to be altered significantly compared with that from healthy individuals.